Do CPO price and capital lead to stock price? The mediating role of profitability - Ashari, Fajar; Sartika, Farahiyah; Sakti, Muhammad Rizky Prima (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2023)
Two factors affect stock prices, internal factors that are directly related to the company which can be seen from the financial statements, namely the capital structure (Debt Equity Ratio) and the profitability or profits obtained by the company (Return on Assets) and external factors related to macroeconomic fundamentals, such as price CPO. The type of data in this research is quantitative data. The research population is a palm oil sector company listed on the Indonesia Stock Exchange from 2020 – 2022. The sample selection technique was carried out based on predetermined criteria so that there were 52 observational data. The analytical tool used in this study is SmartPLS 3. The results show that profitability is not affected by CPO prices, between capital structure and profitability there is a negative and significant effect, and between profitability and stock prices, there also have a negative and significant effect. CPO and DER prices do not affect share prices. Meanwhile, neither CPO prices nor capital structure significantly affect stock prices mediated by profitability